Esquemas maladaptativos en choferes de transporte público de Lima - Abarca Osorio, Cenina (2018)
This article is based on the research whose purpose was to find the early maladaptive schemes developed by drivers belonging to a public transport company in Metropolitan Lima. For the study, the number of drivers’ traffic infractions in a range of ten years perpetuated by 68 drivers between 27 and 70 years was considered.This population was evaluated using the Young Scheme questionnaire 3rd edition. The results indicate that the scheme established in the majority of drivers (77.9%) is the Negativity and Pessimism scheme. Likewise, other schemes were identified such as Mistrust and abuse, Insufficient self-control, submission, self-sacrifice, search for approval and unattainable standards. These results allow to deduce that, by involving at least one scheme of each domain, each of the five basic needs was to a certain degree not sufficiently satisfied and that the most commonly used coping modes are performance and overcompensation.